EFFECT OF Nattrassiae mangiferae ON THE WOOD SOLUBLE AND NON-SOLUBLE CHEMICAL COMPONENT - Aree Adel Abdulqader (Mesopotamia Journal of Agriculture)
The effect of Nattrassiae mangiferae ( H. & P. Sydow ) Sutton & Dyko on the wood soluble chemical components in ethanol – benzene and hot water , showed that the highest lost of these contents were in the willow wood , poplar , sycamore , oak , pine wood respectively. The affect of non-soluble chemical components by the fungus emphasized throughout. a highest alternation in the amount of lignin in pine woods followed by poplar , sycamore , oak and willows wood respectively. Woods content of lignin increased gradually with the continuous of incubation period. The highest lost in ash was found in the willow, sycamore, pine, oak wood, poplar was the lowest, with no effect of the incubation periods. Holocellulose of pine and oak wood showed the lowest lost by the fungus while it was highest in willow and their amounts decreased according to incubating duration.